Call to Arms: The Corps Series #2 - Griffin, W. E. B. (New York : Jove Books, 1987)
The second novel in a series about the Marine Corps follows the first combat operation of the Raiders, a small elite force designed to operate behind enemy lines during World War II.
Keywords: United States -- Marine Corps -- History; World War, 1939-1945 -- Fiction; United States -- History, Military